2012
DOI: 10.1177/0148607112464781
|View full text |Cite
|
Sign up to set email alerts
|

A Parenteral Nutrition Use Survey With Gap Analysis

Abstract: The survey data are a valuable snapshot of current practices with PN. Poor compliance with some of the safe practice guidelines continues. This will help guide new safety initiatives for the PN use process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
127
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 62 publications
(135 citation statements)
references
References 44 publications
2
127
0
6
Order By: Relevance
“…111 Nearly 75% of respondents in a national survey allow nonnutrient medication to be added to PN admixtures. 112 Most frequently included are insulin, heparin, and the histamine type-2 receptor antagonists. Much less commonly included are albumin, digoxin, dopamine, erythropoietin, furosemide, hydrocortisone, methylprednisolone, metoclopramide, octreotide, and ondansetron.…”
Section: Questionmentioning
confidence: 99%
“…111 Nearly 75% of respondents in a national survey allow nonnutrient medication to be added to PN admixtures. 112 Most frequently included are insulin, heparin, and the histamine type-2 receptor antagonists. Much less commonly included are albumin, digoxin, dopamine, erythropoietin, furosemide, hydrocortisone, methylprednisolone, metoclopramide, octreotide, and ondansetron.…”
Section: Questionmentioning
confidence: 99%
“…New analyses are required to understand the impact of these on complication rates in both PN and EN. Safe practice guidelines for PN have been published [Mirtallo et al 2004], but adherence is poor [Boullata et al 2012;Seres et al 2006]. Safety interventions have resulted in significantly reduced infection rates for central venous catheters [Pronovost, 2008], and the acceptable rate is now zero in hospitalized patients [Kuhn, 2008].…”
Section: Enteral Nutrition and Parenteral Nutrition: Recent Developmentsmentioning
confidence: 99%
“…At the time of the survey, only 22% had access to a multi‐oil ILE product (ie, SMOFlipid), with the majority using pure soybean oil ILE in the United States. These data differ slightly from a 2011 survey, which reported that 28% used 3‐in‐1 and 45% used 2‐in‐1 compounded PN in adult patients . It was of great interest to note that only 5 or fewer PN admixtures were prepared by those institutions caring for 50% of adults, 82% of pediatrics, and 64% of neonates .…”
Section: Ile Preparationmentioning
confidence: 62%
“…These data differ slightly from a 2011 survey, which reported that 28% used 3‐in‐1 and 45% used 2‐in‐1 compounded PN in adult patients . It was of great interest to note that only 5 or fewer PN admixtures were prepared by those institutions caring for 50% of adults, 82% of pediatrics, and 64% of neonates . Of the 16% minority using commercial MCB PN products in the United States, nearly 5% add separate ILEs to their 2‐chambered PN .…”
Section: Ile Preparationmentioning
confidence: 73%
See 1 more Smart Citation